UWB Antenna Width Tuning Effect for UWB Communication - Salleh, Azahari; Ali, Nur Alisa; Shairi , N. A; Mohamed Aminuddin, Mai Mariam; Mohamad, Najmiah Radiah; Ja'afar, Abd Shukur; Abd Rahim, Rosman; Mustaffa, Izadora; Mohammed Napiah, Zul Atfyi Fauzan; Zainuddin, Muhammad Noorazlan Shah (AENSI Publisher, 2013)

(untitled)
In this paper, a performance analysis of an array of 2 x 1 Ice Cream Cone UWB Antenna for Ultra Wide Band (UWB) communication is being proposed. The antenna designs have been simulated using CST Microwave Studio. The antenna covers the UWB spectrum from 3.1 to 10.6 GHz, and had a return loss below than -10 dB throughout the entire band. The basic antenna analysis has been done including the analysis of antenna performance due to antenna width tuning. A compact antenna area of 70 x 80 mm2 is obtained. The material used is FR-4 epoxy glass substrate that has dielectric constant, r = 4.4 and the dielectric thickness; h = 1.6mm. The antenna also gives omni-directional radiation characteristics with reasonable gain values over the same frequency band